Conservative management options for morbidly adherent placenta - Satia, Meena N.; Gandhi, Animesh; Shilotri, Manali P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Morbidly adherent placenta is still a very significant cause of obstetric hemorrhage. Methods: A retrospective, descriptive study was undertaken over a period of one and a half year in a tertiary care hospital of all diagnosed cases of morbidly adherent placenta which were managed conservatively and the maternal and perinatal outcomes were noted. Preparation for conservative management of cases of adherent placenta in the antenatal period included informing interventional radiologists and placement of internal iliac balloon catheters just before classical caesarean section. Post-operative methotrexate was used in a few patients. Results: 11 cases of morbidly adherent placenta diagnosed on Doppler ultrasound scan, and confirmed by MRI were identified. All patients underwent classical caesarean section. 9 patients had internal iliac balloon placement. 5 patients received methotrexate. 3 patients required obstetric hysterectomy. 1 maternal and 2 perinatal mortalities were noted. Conclusions: Interventional radiology and methotrexate can be used to avoid peripartum hysterectomy and to optimize maternal and perinatal outcome.